A Protracted Sensitive Period Regulates the Development of Cross-Modal Sound–Shape Associations in Humans. (October 2019) - Sourav, Suddha; Kekunnaya, Ramesh; Shareef, Idris; Banerjee, Seema; Bottari, Davide; Röder, Brigitte
Humans preferentially match arbitrary words containing higher- and lower-frequency phonemes to angular and smooth shapes, respectively. Here, we investigated the role of visual experience in the development of audiovisual and audiohaptic sound–shape associations (SSAs) using a unique set of five groups: individuals who had suffered a transient period of congenital blindness through congenital bilateral dense cataracts before undergoing cataract-reversal surgeries (CC group), individuals with a history of developmental cataracts (DC group), individuals with congenital permanent blindness (CB group), individuals with late permanent blindness (LB group), and controls with typical sight (TS group). Whereas the TS and LB groups showed highly robust SSAs, the CB, CC, and DC groups did not—in any of the modality combinations tested. These results provide evidence for a protracted sensitive period during which aberrant vision prevents SSA acquisition. Moreover, the finding of a systematic SSA in the LB group demonstrates that representations acquired during the sensitive period are resilient to loss despite dramatically changed experience.